"Kitab Al-Muthakar Wa Al-Moanath by Abi Altayeb Alwashaa (325 AH)": Study and Investigation - Al Rfou, Atef Taleb (Journal of Arabic Language Sciences and Literature, 2022)
This research is concerned with editing a manuscript entiteled as "Kitab Al-Muthakar walmoanath Labi Altayeb Alwashaa". Alwashaa mentioned a large, essential lingual material in the chapter about masculine, feminine and combine wordings in this abridged book. He clarified what can be deduced through measurement and marks and what can be known through hearing and narrative with paying attention to reasoning and cause. The author mentioned a large number of poetry verse and of Quran verse. This research is published by accreditation on transcript version that exists in King Abdulaziz General library in Riyadh/ Transcript department ( archive Number: 3065 (2)). This transcript consists of 19 papers, each paper contains 20 lines, average word number is 11 words in each line. This transcript version is a full and a complete version, the first page contains the title, the author name in text hand, some words are written in foreign language letters, others not, it is as previously mentioned a full and complete version. This research seeks to editing this book transcript in a scientific and accurate way, to refine this transcript in the most exact and accurate form as to be close as possible to the form craved by the classifier. It is verified through following scientific integrity, scientific methodology popular at editing Arabic heritage.